Visões/concepções sobre patrimônio histórico em Uberlândia-MG 1950-1988 - Lima, Soene Ozana de (2007)
This work aims at approaching the historic heritage of Uberlândia, by means of the discussion of issues related to the history of buildings that compound the urban landscape. The research seeks to avoid the merely architectonic approaches and to emphasize the meanings built by the dwellers when they visualize squares gardens, monuments and streets. The proposition to be developed in this work relies on the idea that heritage is about memory and life experience of individuals who live, work and live together in the urban space. In this sense, we analyze the institutions of preservation and the different views of the Press, likes those promoted by the journals Correio de Uberlândia and Primeira Hora ; the documentation of public policies and the worker s narratives about preservation. This work permits the study of heritage from several standpoints, and it doesn t confine itself to the official sources and the ruling discourse.